Parallel Lives: Social Comparison Across National Boundaries - Jonathan White (London School of Economics and Political Science (LSE), European Institute, 2012)
The paper presents a distinctive approach to cross-border ties between Europeans. In place of the standard focus on identity or trust, it recommends the study of practices of social comparison, understood as how citizens evoke relevant others for the purpose of situating and evaluating their experiences. The first section offers a conceptual analysis of social comparison, building on and extending social-psychological accounts. The second section shows how the emergence of the European Union presents new opportunities for social comparison. By generating diverse social encounters, new information resources, and an extension in the scope of common legislation, it invites citizens to compare their daily experiences with those of people further afield and to evoke reference groups outside their country of residence. The third section looks at the political significance of these emergent practices, be it for the perception of injustice, the sense of personal misfortune, or the development of new forms of cross-national subjecthood.
Keywords: 330